Media Archeology and "excavation" on Twitter: the birth of #Rio2016 hashtag - Teixeira, Carlos Roberto Gaspar (2020)
The media archeology is a concept that aims to understand the cultural processes through the excavation of media records. This article aims to identify how the hashtag #Rio2016 was created. Tools were used in an "archeological action" that sought digital records on websites to determine the sequence of appearance of the hashtag on Twitter. Based on media archeology concepts, the records retrieval process is presented, as well a reflection about the recovered data.